Methodology for assessing the financial potential of the state in overcoming the consequences of military conflicts - A.Yu. Polchanov (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу, 2018)
The article is devoted to the study of the methodological foundations for measuring the state financial potential in overcoming the consequences of military conflicts. The critical analysis of papers on this subject makes it possible to define 10 quantitative indicators to assess the formation, distribution and use of financial resources to ensure post-conflict recovery. Separately, the author had proposed an indicator of regional concentration of sources of financial resources, which allows assessing the level of financial imbalances at the regional level. Based on data from the State Statistics Service of Ukraine, the National Bank of Ukraine and the World Bank Group, the proposed indicators have been calculated and compared with their recommended values in 2014–2016. The assessment of financial potential of the state through its international credit rating (for example, Fitch Ratings), positions in ratings Doing Business, Global Competitiveness Index, Index of Economic Freedom and Corruption Perceptions Index 2010–2016 has not been left without attention.